Studies on Indian Medical History - Meulenbeld, G.J.,; Wujastyk, D., (Asian Studies - Book Archive pre-2000, 1987)
Papers presented at the International Workshop on the Study of Indian Medicine held at the Wellcome Institute for the History of Medicine, 2-4 September 1985.